Распределенная информационная система моделирования чрезвычайных ситуаций в грид на примере лесных пожаров в АР Крым - Храмов, В.В.; Будник, Н.Н. (Кибернетика и вычислительная техника, 2012)
Рассмотрены методы, связанные с моделированием лесных пожаров в АР Крым с использованием грид-среды при помощи распределенной вычислительной системы моделирования чрезвычайных ситуаций. Описаны ее особенности, архитектура, а также веб-интерфейс пользователя. Получен комплекс альтернативных моделей прогнозирования пожаров, предложены процедуры адаптивной организации вычислительного эксперимента в среде грид. Розглянуто методи, пов'язані з організацією моделювання лісових пожеж в АР Крим з використанням грід-середовища за допомогою розподіленої обчислювальної системи моделювання надзвичайних ситуацій. Наведено опис її особливостей, архітектури, а також веб-інтерфейсу користувача. Одержано комплекс альтернативних моделей прогнозування пожеж, запропоновано процедури адаптивної організації обчислювального експерименту в середовищі грід. The purpose of this article is to examine the methods of modeling of forest fires in the ARC based on the Grid environment, a distributed computing system for simulation of emergency situations, the description of its features and architecture as well as Web-based user interface. The model runs with the distributed simulation emergency system. This article describes the architecture and the interface of this system. The article lists the current approaches and their main problems to the assessment of fire risk. As the result, there was created threedimensional model of forest area on fire. The Basic result is an information Grid system for emergency modeling: The Case of forest fires in the ARC, equipped with convenient and versatile web interface for the Grid environment. Based on the results of this research, there was created an information system modeling emergencies in Grid.